2008
DOI: 10.1253/circj.72.1136
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of Bronchial Arteries Correlates With Extent of Central Disease in Patients With Chronic Thromboembolic Pulmonary Hypertension

Abstract: Background Dilatation of the bronchial arteries is a well-recognized feature in patients with chronic thromboembolic pulmonary hypertension (CTEPH). The purpose of the current study was to use computed tomography (CT) to assess the relationship between dilated bronchial arteries and the extent of thrombi, and to evaluate the predictive value of the former for surgical outcome. Methods and ResultsFifty-nine patients with CTEPH and 16 with pulmonary arterial hypertension (PAH) were retrospectively evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 23 publications
5
33
0
Order By: Relevance
“…The peak of changes in these three morphological parameters appeared to be in the area of total pulmonary arterial occlusion through ligation, while partial and progressive occlusion through repeated emboli generated the same modifications, but to a lesser extent. This observation, at least for bronchial arterial remodelling, is in accordance with findings from a study by SHIMIZU et al [29], whose retrospective analysis of computed tomography angiography from 59 patients with CTEPH showed that the cross-sectional area of the bronchial arteries positively correlated with the central extent of the thromboembolic material compared with obstruction on the segmental level. They also compared the CTEPH group to 16 patients suffering from PAH (group 1 of the Nice classification) and found significant increase in bronchial artery total area of CTEPH patients compared with PAH.…”
Section: Findings In Porcine Histologysupporting
confidence: 92%
See 1 more Smart Citation
“…The peak of changes in these three morphological parameters appeared to be in the area of total pulmonary arterial occlusion through ligation, while partial and progressive occlusion through repeated emboli generated the same modifications, but to a lesser extent. This observation, at least for bronchial arterial remodelling, is in accordance with findings from a study by SHIMIZU et al [29], whose retrospective analysis of computed tomography angiography from 59 patients with CTEPH showed that the cross-sectional area of the bronchial arteries positively correlated with the central extent of the thromboembolic material compared with obstruction on the segmental level. They also compared the CTEPH group to 16 patients suffering from PAH (group 1 of the Nice classification) and found significant increase in bronchial artery total area of CTEPH patients compared with PAH.…”
Section: Findings In Porcine Histologysupporting
confidence: 92%
“…Although we will not discuss this point extensively, since these findings were sparse in our analysis, the phenomenon has been shown for humans and animals under exercise conditions [26][27][28]. The pattern of hypertrophy and enlargement of systemic bronchial arteries is well known in CTEPH [25,29]. It has been speculated that a decrease of postobstructive pulmonary artery pressure and the eventual increase of the pressure gradient between bronchial arteries and pulmonary arteries might lead to an opening of pre-existing bronchopulmonary arterial anastomoses [30,31].…”
Section: Intrapulmonary Systemic Vesselsmentioning
confidence: 89%
“…In contrast to patients with PAH, CTEPH patients may display significant bronchopulmonary collateral blood flow, accounting for up to 30% of systemic blood flow draining directly into the pulmonary veins [29,30]. The presence of bronchial collaterals has been used as a ''biomarker'' for the diagnosis of CTEPH [31]. A linear correlation exists between the magnitude of bronchosystemic shunt and dilatation of the bronchial arteries in patients with CTEPH [32].…”
Section: Pulmonary Vascular Remodellingmentioning
confidence: 99%
“…In fact, chronic PE is more frequently associated with dilated bronchial arteries than acute PE as seen on CTPA [51,52]. Interestingly, systemic blood flow may increase by up to 30% with PE, in comparison to the original blood flow [53,54].…”
Section: Chronic Pulmonary Embolism Dual-energy Ctmentioning
confidence: 99%